Latin American networking and cooperative struggles in Argentina: A conversation with the Movimiento de Ocupantes e Inquilinos (MOI) - Néstor Jeifetz; Ana Vilenica; Moisés Quiroz (Radical Housing Journal, 2024)
This conversation examines the Movimiento de Ocupantes e Inquilinos (MOI) in Argentina, a grassroots organization promoting cooperative, self-managed housing for over 30 years. Based on a conversation with Néstor Jeifetz, the article traces the origins of the MOI from the 1980s building occupations in Buenos Aires, through its connection to the broader Latin American cooperative housing movement, including the creation of the Latin American Secretariat for Popular Housing and Habitat (SELVIHP). The article explores how MOI’s efforts to reclaim vacant urban properties—such as the La Fábrica cooperative housing project—address the critical need for secure, affordable housing in a context of neoliberal economic policies and external debt crises. Jeifetz discusses the political ramifications of recent far-right victories in Argentina, which threaten hard-won social rights and self-managed housing initiatives, as well as the MOI’s role in resisting these policies through a framework of collective ownership, democratic decision-making, and mutual aid. By highlighting the intersections of housing with education, health, and labor, and situating the MOI’s work within a larger history of land and building occupations across Abya-Yala, this article provides a nuanced understanding of the ongoing struggles for housing justice in the face of both local and global neoliberal forces.